Acacetin suppresses the electrocardiographic and arrhythmic manifestations of the J wave syndromes - Di Diego, José M. (PLoS One, 2020)
BACKGROUND: J wave syndromes (JWS), including Brugada (BrS) and early repolarization syndromes (ERS), are associated with increased risk for life-threatening ventricular arrhythmias. Pharmacologic approaches to therapy are currently very limited. Here, we evaluate the effects of the natural flavone acacetin. METHODS: The effects of acacetin on action potential (AP) morphology and transient outward current (I(to)) were first studied in isolated canine RV epicardial myocytes using whole-cell patch clamp techniques. Acacetin’s effects on transmembrane APs, unipolar electrograms and transmural ECGs were then studied in isolated coronary-perfused canine RV and LV wedge preparations as well as in whole-heart, Langendorff-perfused preparations from which we recorded a 12 lead ECG and unipolar electrograms. Using floating glass microelectrodes we also recorded transmembrane APs from the RVOT of the whole-heart model. The I(to) agonist NS5806, sodium channel blocker ajmaline, calcium channel blocker verapamil or hypothermia (32°C) were used to pharmacologically mimic the genetic defects and conditions associated with JWS, thus eliciting prominent J waves and provoking VT/VF. RESULTS: Acacetin (5–10 μM) reduced I(to) density, AP notch and J wave area and totally suppressed the electrocardiographic and arrhythmic manifestation of both BrS and ERS, regardless of the experimental model used. In wedge and whole-heart models of JWS, increasing I(to) with NS5806, decreasing I(Na) or I(Ca) (with ajmaline or verapamil) or hypothermia all resulted in accentuation of epicardial AP notch and ECG J waves, resulting in characteristic BrS and ERS phenotypes. Phase 2-reentrant extrasystoles originating from the RVOT triggered VT/VF. The J waves in leads V1 and V2 were never associated with a delay of RVOT activation and always coincided with the appearance of the AP notch recorded from RVOT epicardium. All repolarization defects giving rise to VT/VF in the BrS and ERS models were reversed by acacetin, resulting in total suppression of VT/VF. CONCLUSIONS: We present experimental models of BrS and ERS capable of recapitulating all of the ECG and arrhythmic manifestations of the JWS. Our findings provide definitive support for the repolarization but not the depolarization hypothesis proposed to underlie BrS and point to acacetin as a promising new pharmacologic treatment for JWS.